Computational screening of chalcones acting against topoisomerase IIα and their cytotoxicity towards cancer cell lines. (1st January 2019) - Sangpheak, Kanyani; Mueller, Monika; Darai, Nitchakan; Wolschann, Peter; Suwattanasophon, Chonticha; Ruga, Ritbey; Chavasiri, Warinthon; Seetaha, Supaporn; Choowongkomon, Kiattawee; Kungwan, Nawee; Rungnim, Chompoonut; Rungrotmongkol, Thanyada
Abstract: Targeted cancer therapy has become one of the high potential cancer treatments. Human topoisomerase II (hTopoII), which catalyzes the cleavage and rejoining of double-stranded DNA, is an important molecular target for the development of novel cancer therapeutics. In order to diversify the pharmacological activity of chalcones and to extend the scaffold of topoisomerase inhibitors, a series of chalcones was screened against hTopoIIα by computational techniques, and subsequently tested for their in vitro cytotoxicity. From the experimental IC50 values, chalcone 3d showed a high cytotoxicity with IC50 values of 10.8, 3.2 and 21.1 µM against the HT-1376, HeLa and MCF-7 cancer-derived cell lines, respectively, and also exhibited an inhibitory activity against hTopoIIα-ATPase that was better than the known inhibitor, salvicine. The observed ligand–protein interactions from a molecular dynamics study affirmed that 3d strongly interacts with the ATP-binding pocket residues. Altogether, the newly synthesised chalcone 3d has a high potential to serve as a lead compound for topoisomerase inhibitors.